A water-based binder and its preparation method and use

By developing an aqueous binder containing multiple monomer units, the polar groups in the polymer form hydrogen bonds or chemical bonds with the silicon material to form a three-dimensional network structure, the lithium-ion battery silicon negative electrode material is solved. The problem of volume expansion and contraction during discharge significantly improves the cycling performance and flexibility of the battery.

CN116190658BActive Publication Date: 2025-02-14SHENZHEN YANYI NEW MATERIALS CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310212349.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-07
Publication Date
2025-02-14
Estimated Expiration
2043-03-07

AI Technical Summary

Technical Problem

The silicon negative electrode material of existing lithium-ion batteries expands and contracts severely during charging and discharging, resulting in fast electrode capacity decay and poor circulation performance. The existing binders cannot effectively suppress this problem.

Method used

Developed an aqueous binder consisting of a polymer containing at least three monomer units by introducing acrylamide, vinyl ether and acrylonitrile monomers into the polymer and by oxidation The prototype initiator undergoes polymerization reaction to form a polymer with high bonding properties and flexibility.

Benefits of technology

The aqueous binder can significantly inhibit the expansion of the silicon negative electrode, improve the circulation performance of the battery, and make the prepared electrode sheet have excellent flexibility and extend the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116190658B_ABST
    Figure CN116190658B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of lithium-ion batteries, and specifically relates to an aqueous binder and a preparation method and use thereof, wherein the aqueous binder comprises a polymer containing at least three monomer units, wherein the polymer comprises a first monomer unit, a second monomer unit and a third monomer unit, wherein the first monomer unit has a structure shown in formula I, the second monomer unit has a structure shown in formula II, and the third monomer unit has a structure shown in formula III, wherein R1, R2, R3 and R6 are the same or different, and each independently represents hydrogen, a linear alkyl group or a branched alkyl group; and R5 is a group containing a hydroxyl group at the end group. The aqueous binder provided by the present invention has excellent bonding properties, can significantly inhibit the expansion of a silicon negative electrode, and at the same time enables the prepared pole piece to have excellent flexibility, thereby improving the cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a water-based binder and a preparation method and application thereof. Background Art

[0002] Nowadays, lithium-ion batteries have been widely used in products such as mobile phones, computers and electric vehicles, and have great commercial value. At present, the positive electrode materials of commercial lithium-ion batteries are mainly oxides such as LiCoO2, LiMn2O4 and LiFePO4; the negative electrode materials are mainly graphite. Due to the low theoretical capacity of graphite (372mAh / g), it is difficult to meet the needs of the rapid development of today's electronic information and energy technology. Therefore, the development of high-capacity silicon-based materials has become a major issue in the development of lithium-ion battery technology. However, due to the greater volume expansion and contraction of silicon-based materials during charging and discharging (up to 300%), the electrode capacity decays quickly and the cycle performance is poor. Therefore, it is necessary to develop a binder with high bonding strength and the ability to reduce the expansion of silicon negative electrodes to achieve the cycle stability of high-capacity negative electrodes.

[0003] Commonly used silicon negative electrode binders in the prior art include SBR (styrene-butadiene rubber) binders and PAA binders. SBR binders are usually used in combination with CMC. SBR itself has low strength, poor bonding strength, and poor inhibition of pole piece expansion. Therefore, when used in silicon negative electrodes, its cycle performance is often very poor. The pole pieces prepared using the PAA binders in the prior art have poor flexibility and processing performance. The pole piece structure is difficult to recover after being damaged, and the cycle performance is poor.

[0004] Therefore, developing an adhesive with excellent bonding properties, flexibility and cycle performance to meet the application requirements of high-performance electrode plates and lithium-ion batteries is an urgent problem to be solved in this field. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide an aqueous binder and a preparation method and use thereof. The aqueous binder provided by the present invention has excellent bonding properties, can significantly inhibit the expansion of the silicon negative electrode, and at the same time makes the prepared electrode have excellent flexibility, thereby improving the cycle performance of the battery.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides an aqueous binder, the aqueous binder comprising a polymer containing at least three monomer units, the polymer comprising a first monomer unit, a second monomer unit and a third monomer unit, the first monomer unit having a structure shown in formula I, the second monomer unit having a structure shown in formula II, the third monomer unit having a structure shown in formula III,

[0008]

[0009] Wherein, R1, R2, R3 and R6 are the same or different and independently represent hydrogen, a straight-chain alkyl group or a branched-chain alkyl group; R5 is a group having a hydroxyl group at the terminal.

[0010] Here, the selection of R1, R2, and R3 is based on the principle of maintaining the water solubility of the monomer, and the selection of R5 is based on the principle of maintaining the water solubility of the monomer.

[0011] The aqueous binder provided by the present invention has excellent bonding performance, can significantly inhibit the expansion of the silicon negative electrode, and at the same time enables the prepared pole piece to have excellent flexibility, thereby improving the cycle performance of the battery.

[0012] In the above aqueous binder, as a preferred embodiment, R5 represents a linear alkyl group having 1 to 6 carbon atoms substituted by a hydroxyl group, a branched alkyl group having 1 to 6 carbon atoms substituted by a hydroxyl group, -CH2CH2OCH2CH2OH or -(CH2CH2O) n H, n≥3 (for example, n can be 3, 5, 7 or 10, etc.).

[0013] In the above aqueous binder, as a preferred embodiment, R1, R2, R3 and R6 are the same or different, and each independently represents hydrogen, a straight-chain alkyl group having 1 to 6 carbon atoms, or a branched-chain alkyl group having 1 to 6 carbon atoms.

[0014] In the above aqueous binder, as a preferred embodiment, R5 represents -CH2CH2OH, CH2CH2CH2OH, -CH2CH2OCH2CH2OH or -(CH2CH2O) n H, n≥3 (for example, n can be 3, 5, 7 or 10, etc.).

[0015] In the above-mentioned aqueous binder, as a preferred embodiment, R1 represents hydrogen, methyl, ethyl, propyl, -CH(CH3)2, -CH2CH2CH2CH3 or -CH2CH(CH3)2; R2 represents hydrogen, methyl, ethyl, propyl, -CH(CH3)2, -CH2CH2CH2CH3 or -CH2CH(CH3)2; R3 represents hydrogen, methyl, ethyl, propyl, -CH(CH3)2, -CH2CH2CH2CH3 or -CH2CH(CH3)2; R6 represents hydrogen, methyl, ethyl or -CH(CH3)2.

[0016] In the above aqueous binder, as a preferred embodiment, the polymer further comprises a fourth monomer unit, and the fourth monomer unit has a structure shown in Formula IV:

[0017]

[0018] Wherein, R4 represents hydrogen, a linear alkyl group or a branched alkyl group; M represents H, Li, Na or K.

[0019] In the above aqueous binder, as a preferred embodiment, R4 represents hydrogen, a straight-chain alkyl group having 1-6 carbon atoms, or a branched-chain alkyl group having 1-6 carbon atoms. For example, R4 represents hydrogen, methyl, ethyl, or -CH(CH3)2.

[0020] In the above-mentioned aqueous binder, as a preferred embodiment, the solid content of the aqueous binder is 9.5-10.5%, and the viscosity is 8000-30000 cps (for example, the viscosity can be 8000 cps, 10000 cps, 15000 cps, 20000 cps, 25000 cps or 30000 cps, etc.).

[0021] In the above aqueous binder, as a preferred embodiment, the polymer has a structure shown in Formula V:

[0022]

[0023] Wherein, M represents H, Li, Na or K;

[0024] R1 represents hydrogen, a straight-chain alkyl group or a branched-chain alkyl group. Preferably, R1 represents hydrogen, a straight-chain alkyl group having 1 to 6 carbon atoms or a branched-chain alkyl group having 1 to 6 carbon atoms. More preferably, R1 represents hydrogen, methyl, ethyl, propyl, -CH(CH3)2, -CH2CH2CH2CH3 or -CH2CH(CH3)2;

[0025] R2 represents hydrogen, a straight-chain alkyl group or a branched-chain alkyl group. Preferably, R2 represents hydrogen, a straight-chain alkyl group having 1 to 6 carbon atoms or a branched-chain alkyl group having 1 to 6 carbon atoms. More preferably, R2 represents hydrogen, methyl, ethyl, propyl, -CH(CH3)2, -CH2CH2CH2CH3 or -CH2CH(CH3)2;

[0026] R3 represents hydrogen, a straight-chain alkyl group or a branched-chain alkyl group. Preferably, R3 represents hydrogen, a straight-chain alkyl group having 1 to 6 carbon atoms or a branched-chain alkyl group having 1 to 6 carbon atoms. More preferably, R3 represents hydrogen, methyl, ethyl, propyl, -CH(CH3)2, -CH2CH2CH2CH3 or -CH2CH(CH3)2;

[0027] R4 represents hydrogen, a straight-chain alkyl group or a branched-chain alkyl group. Preferably, R4 represents hydrogen, a straight-chain alkyl group having 1 to 6 carbon atoms or a branched-chain alkyl group having 1 to 6 carbon atoms. For example, R4 represents hydrogen, methyl, ethyl or -CH(CH3)2;

[0028] R5 is a group containing a hydroxyl group at the end. Preferably, R5 represents a straight-chain alkyl group having 1 to 6 carbon atoms substituted by a hydroxyl group, a branched-chain alkyl group having 1 to 6 carbon atoms substituted by a hydroxyl group, -CH2CH2OCH2CH2OH or -(CH2CH2O) n H, n≥3, more preferably, said R5 represents -CH2CH2OH, CH2CH2CH2OH, -CH2CH2OCH2CH2OH or -(CH2CH2O) n H, n≥3;

[0029] R6 represents hydrogen, a straight-chain alkyl group or a branched-chain alkyl group. Preferably, R6 represents hydrogen, a straight-chain alkyl group having 1 to 6 carbon atoms or a branched-chain alkyl group having 1 to 6 carbon atoms. More preferably, R6 represents hydrogen, a methyl group, an ethyl group or -CH(CH3)2;

[0030] a:b:c:d=(30~80):(0~50):(5~50):(5-30), for example, a:b:c:d can be 40:30:15:15, 40:30:10:20, 60:0:20:20, 30:20:40:10 or 30:20:20:30, etc.; a:b:c:d is the molar ratio of each monomer unit.

[0031] In a second aspect, the present invention provides a method for preparing the aqueous binder as described in the first aspect, comprising the following steps:

[0032] Under the action of an initiator, the polymer monomers undergo a polymerization reaction in a reaction solvent to obtain the water-based binder, wherein the polymer monomers include acrylamide monomers, vinyl ether monomers and acrylonitrile monomers.

[0033] The aqueous binder prepared by the preparation method provided by the present invention has high bonding force, can significantly inhibit the expansion of the silicon negative electrode, and improve the cycle performance of the battery.

[0034] In the above method for preparing the aqueous binder, as a preferred embodiment, the polymer monomer further includes an acrylic monomer.

[0035] In the preparation method of the above-mentioned aqueous adhesive, as a preferred embodiment, the molar ratio of the acrylamide monomer, the acrylic acid monomer, the vinyl ether monomer and the acrylonitrile monomer is (30-80):(0-50):(5-50):(5-30), for example, it can be 40:30:15:15, 40:30:10:20, 60:0:20:20, 30:20:40:10 or 30:20:20:30, etc.

[0036] In the preparation method of the above-mentioned water-based adhesive, as a preferred embodiment, taking the total molar number of the acrylamide monomer, the acrylic acid monomer, the vinyl ether monomer and the acrylonitrile monomer as 100%, the molar percentage of the acrylamide monomer is 30% to 80%, the molar percentage of the acrylic acid monomer is 0% to 50%, the molar percentage of the vinyl ether monomer is 5% to 50%, and the molar percentage of the acrylonitrile monomer is 5% to 30%.

[0037] If the molar percentage of the vinyl ether monomer is too large, the water solubility of the aqueous adhesive is poor and the mechanical strength is low. If the molar percentage of the vinyl ether monomer is too small, the flexibility of the aqueous adhesive is poor.

[0038] In the above-mentioned method for preparing the aqueous binder, as a preferred embodiment, the acrylamide monomer has a structure shown in formula VI, the vinyl ether monomer has a structure shown in formula VII, the acrylonitrile monomer has a structure shown in formula VIII, and the acrylic acid monomer has a structure shown in formula IX.

[0039]

[0040] Wherein, the definitions of M, R1, R2, R3, R4, R5 and R6 are the same as those of M, R1, R2, R3, R4, R5 and R6 in the aqueous adhesive described in the first aspect.

[0041] In the preparation method of the aqueous binder, as a preferred embodiment, based on the total molar number of the polymer monomer as 100%, the molar number of the initiator is 0.02% to 1.0%, for example, it can be 0.02%, 0.1%, 0.3%, 0.6% or 1%.

[0042] In the above-mentioned method for preparing the water-based binder, as a preferred embodiment, the polymer monomer is polymerized in a reaction solvent under the action of an initiator to obtain the water-based binder, comprising the following steps:

[0043] S1, adding the polymer monomer into a reaction solvent, stirring and dispersing, and obtaining a mixed solution;

[0044] S2, adding the initiator to the mixed solution to carry out polymerization reaction, and after the reaction is completed, vacuuming, alkali neutralization, sieving, and demagnetization are carried out to obtain the water-based binder.

[0045] Here, the aqueous binder may be a water-soluble binder for silicon negative electrode.

[0046] In the above method for preparing the aqueous binder, as a preferred embodiment, the reaction solvent is water, preferably deionized water.

[0047] In the above method for preparing the aqueous binder, as a preferred embodiment, in step S1, the stirring speed is 100-800 rpm, for example, 100 rpm, 300 rpm, 500 rpm or 800 rpm.

[0048] In the above-mentioned method for preparing the aqueous binder, as a preferred embodiment, in step S1, after the polymer monomer is added to the reaction solvent, an inert gas is introduced to remove oxygen in the mixed solution.

[0049] In the above method for preparing the aqueous binder, as a preferred embodiment, the inert gas is nitrogen or argon.

[0050] In the above method for preparing the aqueous binder, as a preferred embodiment, the initiator is a water-soluble initiator.

[0051] In the preparation method of the above-mentioned aqueous binder, as a preferred embodiment, the initiator includes at least one of sodium persulfate, potassium persulfate, ammonium persulfate, ammonium persulfate / sodium sulfite, ammonium persulfate / sodium bisulfite, and hydrogen peroxide / ferrous ion.

[0052] In the preparation method of the above-mentioned aqueous adhesive, as a preferred embodiment, the adding the initiator to the mixed solution to carry out a polymerization reaction includes: adding a first initiator to the mixed solution to carry out a first polymerization reaction, and then adding a second initiator to carry out a second polymerization reaction.

[0053] In the preparation method of the above-mentioned aqueous binder, as a preferred embodiment, the molar ratio of the first initiator to the second initiator is (0.5-3):1, for example, it can be 0.5:1, 1:1, 1.5:1, 2:1 or 3:1.

[0054] In the above method for preparing the aqueous binder, as a preferred embodiment, the first initiator includes at least one of sodium persulfate, potassium persulfate, and ammonium persulfate.

[0055] In the preparation method of the above-mentioned water-based adhesive, as a preferred embodiment, the second initiator is a redox initiator, including at least one of ammonium persulfate / sodium sulfite, ammonium persulfate / sodium bisulfite, and hydrogen peroxide / ferrous ion.

[0056] Here, the ferrous ion may be a ferrous salt, such as ferrous sulfate, ferrous chloride, and the like.

[0057] The preparation method provided by the present invention can further react the residual monomers and increase the reaction rate by adding a second initiator and limiting the second initiator to a redox initiator, thereby making the polymerization reaction more complete.

[0058] In the preparation method of the above-mentioned water-based adhesive, as a preferred embodiment, the temperature of the first polymerization reaction is 40℃~80℃ (for example, it can be 40℃, 45℃, 50℃, 55℃, 60℃, 70℃ or 80℃, etc.), and the time is 3~10h (for example, it can be 3h, 5h, 7h or 10h, etc.); the temperature of the second polymerization reaction is 70℃~90℃ (for example, it can be 70℃, 80℃ or 90℃, etc.), and the time is 1-3h (for example, it can be 1h, 2h or 3h, etc.).

[0059] In the preparation method of the above-mentioned aqueous adhesive, as a preferred embodiment, in step S2, vacuum is applied for 1 to 2 hours, and the absolute vacuum degree is 5 to 50 KPa (for example, 5 KPa, 10 KPa, 15 KPa, 20 KPa, 40 KPa or 50 KPa, etc.), preferably 10 to 20 KPa.

[0060] In the preparation method of the above-mentioned aqueous binder, as a preferred embodiment, in step S2, the alkali neutralization includes neutralization using lithium hydroxide, sodium hydroxide or potassium hydroxide to a pH value of 6.0 to 9.0 (for example, 6.0, 7.0, 8.0 or 9.0, etc.).

[0061] In the above method for preparing the water-based adhesive, as a preferred embodiment, in step S2, the mesh size of the sieve is 150-400 meshes, for example, 150 meshes, 200 meshes, 300 meshes or 400 meshes.

[0062] In the above-mentioned method for preparing the aqueous binder, as a preferred embodiment, in step S2, the demagnetization is performed using a super-strong magnetic rod demagnetizer. Since the prepared aqueous binder will be used in secondary batteries, the demagnetization treatment is performed according to the requirements of its application field.

[0063] In the above method for preparing the aqueous binder, as a preferred embodiment, in step S2, after the alkali neutralization and before the sieving, the solid content is adjusted to 10±0.5%.

[0064] In a third aspect, the present invention provides a use of the aqueous binder according to the first aspect or the aqueous binder prepared by the preparation method of the aqueous binder according to the second aspect, wherein the aqueous binder is used for preparing a lithium ion battery.

[0065] Among the uses of the above-mentioned aqueous binder, as a preferred embodiment, the aqueous binder is used for preparing negative electrode sheets in lithium-ion batteries.

[0066] The method of using a binder to prepare a negative electrode of a battery is well known to those skilled in the art. Preferably, a method of using the binder of the present invention to prepare a negative electrode sheet is as follows:

[0067] The binder, the conductive agent and the active material of the present invention are mixed in deionized water, and the obtained slurry is coated on a current collector to prepare a negative electrode sheet.

[0068] In the above-mentioned use of the aqueous binder, as a preferred embodiment, the negative electrode active material in the negative electrode sheet includes a silicon-based material.

[0069] Compared with the prior art, the beneficial effects of the present invention include at least one of the following:

[0070] (1) The aqueous binder provided by the present invention has excellent bonding properties, can significantly inhibit the expansion of the silicon negative electrode, and at the same time makes the prepared electrode sheet have excellent flexibility, thereby improving the cycle performance of the battery.

[0071] (2) The present invention uses acrylamide and its derivatives, acrylonitrile and its derivatives and vinyl ether monomers to carry out free radical polymerization in aqueous solution to obtain a water-soluble polymer with a certain degree of flexibility. The polar groups -OH, -CONR2R3, -CN, etc. in the polymer form hydrogen bonds or chemical bonds with silicon particles in the silicon negative electrode, thereby increasing the interaction between the silicon material and graphite, and the binder and the active material, forming a three-dimensional network structure, thereby improving the bonding force while reducing the expansion of the silicon negative electrode and greatly improving its cycle life. DETAILED DESCRIPTION

[0072] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.

[0073] The embodiments of the present invention are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and processes are given, but the protection scope of the present invention is not limited to the following embodiments. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.

[0074] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0075] The process parameters in the following examples that do not specify specific conditions are usually based on conventional conditions. The experimental reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the amounts of the experimental reagents, unless otherwise specified, are all the amounts of reagents used in conventional experimental operations.

[0076] In a first aspect, an embodiment of the present invention provides an aqueous binder, the aqueous binder comprising a polymer containing at least three monomer units, the polymer comprising a first monomer unit, a second monomer unit and a third monomer unit, the first monomer unit having a structure shown in formula I, the second monomer unit having a structure shown in formula II, the third monomer unit having a structure shown in formula III,

[0077]

[0078] wherein R1 represents hydrogen, methyl, ethyl, propyl, -CH(CH3)2, -CH2CH2CH2CH3 or -CH2CH(CH3)2; R2 represents hydrogen, methyl, ethyl, propyl, -CH(CH3)2, -CH2CH2CH2CH3 or -CH2CH(CH3)2; R3 represents hydrogen, methyl, ethyl, propyl, -CH(CH3)2, -CH2CH2CH2CH3 or -CH2CH(CH3)2; R6 represents hydrogen, methyl, ethyl or -CH(CH3)2; R5 represents -CH2CH2OH, CH2CH2CH2OH, -CH2CH2OCH2CH2OH or -(CH2CH2O) n H, n≥3;

[0079] The polymer further comprises a fourth monomer unit, and the fourth monomer unit has a structure shown in Formula IV:

[0080]

[0081] wherein R4 represents hydrogen, methyl, ethyl or -CH(CH3)2; M represents H, Li, Na or K;

[0082] The polymer has a structure shown in Formula V:

[0083]

[0084] Wherein, the definitions of M, R1, R2, R3, R4, R5 and R6 are the same as those of M, R1, R2, R3, R4, R5 and R6 in the embodiment of the present invention, and a:b:c:d=(30-80):(0-50):(5-50):(5-30);

[0085] The aqueous binder also includes water. The solid content of the aqueous binder is 9.5-10.5% and the viscosity is 8000-30000 cps.

[0086] The invention discloses a water-soluble binder for silicon negative electrode of lithium ion battery and a preparation method thereof, and aims to solve the problem that traditional binders are applied to high silicon negative electrode (gram capacity ≥ 500 mAh / g), which has low bonding force, excessive expansion and poor cycle performance.

[0087] The present invention introduces a hydroxyl-containing monomer on the basis of a commonly used PAA-type binder, and the obtained binder has high strength and certain flexibility. When applied to a high-silicon negative electrode, it is conducive to the dispersion of the conductive agent and the negative electrode material. The polar groups on the polymer can form strong hydrogen bonds and chemical bonds with the polar groups on the surface of the silicon material, thereby forming a three-dimensional cross-linked network structure as a whole, while improving the bonding force, reducing the expansion of the silicon negative electrode and greatly improving its cycle life. In addition, after introducing a cyano group with better complexing ability, the bonding force will be further improved.

[0088] In a second aspect, an embodiment of the present invention provides a method for preparing the aqueous binder as described in the first aspect, comprising the following steps:

[0089] S1. Add polymer monomers into deionized water, stir and disperse to obtain a mixed solution, and introduce inert gas to remove oxygen in the mixed solution, wherein the stirring speed is 100-800 rpm, the inert gas is nitrogen or argon, the polymer monomers include acrylamide monomers, vinyl ether monomers and acrylonitrile monomers, and the polymer monomers also include acrylic acid monomers, and the molar ratio of the acrylamide monomers, acrylic acid monomers, vinyl ether monomers and acrylonitrile monomers is (30-80):(0-50):(5-50):(5-30); the acrylamide monomer has a structure shown in formula VI, the vinyl ether monomer has a structure shown in formula VII, the acrylonitrile monomer has a structure shown in formula VIII, and the acrylic acid monomer has a structure shown in formula IX.

[0090]

[0091] Wherein, the definitions of M, R1, R2, R3, R4, R5 and R6 are the same as those of M, R1, R2, R3, R4, R5 and R6 in the aqueous adhesive described in the first aspect.

[0092] S2. Add a first initiator to the mixed solution to carry out a first polymerization reaction, then add a second initiator to carry out a second polymerization reaction, and after the reaction is completed, evacuate for 1 to 2 hours to an absolute vacuum degree of 5 to 50 KPa, then perform alkali neutralization, sieve, and demagnetize to obtain the aqueous binder, wherein the sum of the molar numbers of the first initiator and the second initiator is 0.02% to 1.0% based on the total molar number of the polymer monomer as 100%; the molar ratio of the first initiator to the second initiator is (0.5 to 3):1, the first initiator includes at least one of sodium persulfate, potassium persulfate, and ammonium persulfate, and the The second initiator is a redox initiator, including at least one of ammonium persulfate / sodium sulfite, ammonium persulfate / sodium bisulfite, and hydrogen peroxide / ferrous ion. The temperature of the first polymerization reaction is 40°C to 80°C, and the time is 3 to 10 hours; the temperature of the second polymerization reaction is 70°C to 90°C, and the time is 1-3 hours. The alkali neutralization includes neutralization with lithium hydroxide, sodium hydroxide or potassium hydroxide to a pH value of 6.0 to 9.0. The mesh number of the sieve is 150 to 400 meshes. In the demagnetization, a super strong magnetic rod demagnetizer is used for demagnetization. After the alkali neutralization and before the sieving, the solid content is adjusted to 10±0.5%.

[0093] In a third aspect, an embodiment of the present invention provides a use of an aqueous binder according to the aqueous binder described in the first aspect or an aqueous binder prepared by the preparation method of the aqueous binder described in the second aspect, wherein the aqueous binder is used for preparing a negative electrode sheet in a lithium-ion battery, wherein the negative electrode active material in the negative electrode sheet includes a silicon-based material.

[0094] In order to further understand the present invention, the water-based binder provided by the present invention and its preparation method and use are described in detail below in conjunction with embodiments. The protection scope of the present invention is not limited by the following embodiments.

[0095] Example 1

[0096] The aqueous binder provided in this embodiment includes a polymer having the following structure:

[0097]

[0098] Among them, a:b:c:d=40:30:15:15.

[0099] The preparation method of the water-based binder provided in this embodiment comprises the following steps:

[0100] 300 g of deionized water was added to the reactor at room temperature, and then 0.4 mol of acrylamide, 0.3 mol of acrylic acid, 0.15 mol of vinyl glycol ether and 0.15 mol of acrylonitrile were added in sequence, and the mixture was stirred and dispersed at a stirring speed of 200 rpm. Nitrogen was introduced (nitrogen flow rate was 2 L / h) for 1 hour to remove oxygen in the solution system (mixed solution), and then the temperature was raised to 50° C. After the temperature was stable, 0.001 mol of initiator potassium persulfate was added to carry out polymerization reaction for 7 hours; the temperature was adjusted to 80° C., and then redox reaction was added. The prototype initiator ammonium persulfate 0.001mol and sodium bisulfite 0.001mol are used for polymerization reaction, and the reaction is carried out for 2h to remove the residual monomers. After the reaction is completed, the vacuum is evacuated for 1h to an absolute vacuum degree of 10KPa to further remove the residual monomers. Then, lithium hydroxide monohydrate is added for neutralization to a pH value of 7.5, and deionized water is added for dilution to obtain a light yellow glue solution. The glue solution is sieved through a 150-mesh sieve and demagnetized using a super strong magnetic rod demagnetizer to obtain the target product (aqueous binder). The solid content of the aqueous binder is 10.4% and the viscosity is 21500cps.

[0101] Example 2

[0102] The aqueous binder provided in this embodiment includes a polymer having the following structure:

[0103]

[0104] Among them, a:b:c:d=40:30:10:20.

[0105] The preparation method of the water-based binder provided in this embodiment comprises the following steps:

[0106] 400 g of deionized water was added to the reactor at room temperature, and then 0.4 mol of acrylamide, 0.3 mol of acrylic acid, 0.1 mol of vinyl glycol ether and 0.2 mol of methacrylonitrile were added in sequence, and the mixture was stirred and dispersed at a stirring speed of 200 rpm. Nitrogen was introduced (nitrogen flow rate 2 L / h) for 1 hour to remove oxygen in the solution system (mixed solution), and then the temperature was raised to 60° C. After the temperature stabilized, 0.0015 mol of initiator ammonium persulfate was added to carry out polymerization reaction for 5 hours; the temperature was adjusted to 80° C., and then an oxidizing agent was added. Reduction initiator ammonium persulfate 0.001mol and sodium bisulfite 0.001mol, polymerization reaction, reaction for 2h to remove residual monomers, after completion of the reaction, evacuate for 1h to an absolute vacuum of 8KPa to further remove residual monomers, then add lithium hydroxide monohydrate for neutralization to pH 7.6, add deionized water to dilute, to obtain a light yellow glue, the glue is sieved through a 150-mesh sieve, and demagnetized using a super strong magnetic rod demagnetizer to obtain the target product (water-based adhesive), the solid content of the water-based adhesive is 10.2%, and the viscosity is 14600cps.

[0107] Example 3

[0108] The aqueous binder provided in this embodiment includes a polymer having the following structure:

[0109]

[0110] Among them, a:c:d=60:20:20.

[0111] The preparation method of the water-based binder provided in this embodiment comprises the following steps:

[0112] 300 g of deionized water was added to the reactor at room temperature, and then 0.6 mol of acrylamide, 0.2 mol of vinyl diethylene glycol ether and 0.2 mol of acrylonitrile were added in sequence, and the mixture was stirred and dispersed at a stirring speed of 400 rpm. Nitrogen was introduced (nitrogen flow rate 2 L / h) for 1 hour to remove oxygen in the solution system (mixed solution), and then the temperature was raised to 50° C. After the temperature stabilized, 0.001 mol of initiator potassium persulfate was added to carry out polymerization reaction for 7 hours; the temperature was adjusted to 80° C., and then a redox initiator persulfate was added. 0.001 mol of ammonium sulfate and 0.001 mol of sodium bisulfite are used for polymerization reaction, and the reaction is carried out for 2 hours to remove residual monomers. After the reaction is completed, vacuum is evacuated for 1 hour to an absolute vacuum degree of 12 KPa to further remove residual monomers, and then lithium hydroxide monohydrate is added for neutralization to a pH value of 7.7, and deionized water is added for dilution to obtain a light yellow glue solution, which is sieved through a 150-mesh sieve and demagnetized using a super strong magnetic rod demagnetizer to obtain the target product (aqueous binder) having a solid content of 10.2% and a viscosity of 17000 cps.

[0113] Example 4

[0114] The aqueous binder provided in this embodiment includes a polymer having the following structure:

[0115]

[0116] Among them, a:b:c:d=30:20:40:10.

[0117] The preparation method of the water-based binder provided in this embodiment comprises the following steps:

[0118] 400 g of deionized water was added to the reactor at room temperature, and then 0.3 mol of acrylamide, 0.2 mol of methacrylic acid, 0.4 mol of vinyl glycol ether and 0.1 mol of acrylonitrile were added in sequence, and the mixture was stirred and dispersed at a stirring speed of 200 rpm. Nitrogen was introduced (nitrogen flow rate 2 L / h) for 1 hour to remove oxygen in the solution system (mixed solution), and then the temperature was raised to 50° C. After the temperature stabilized, 0.001 mol of initiator potassium persulfate was added to carry out polymerization reaction for 7 hours; the temperature was adjusted to 80° C., and then redox reaction was added. The prototype initiator ammonium persulfate 0.001mol and sodium bisulfite 0.001mol are used for polymerization reaction, and the reaction is carried out for 2h to remove the residual monomers. After the reaction is completed, the vacuum is evacuated for 1h to an absolute vacuum degree of 15KPa to further remove the residual monomers. Then, lithium hydroxide monohydrate is added for neutralization to a pH value of 7.7, and deionized water is added for dilution to obtain a light yellow glue solution. The glue solution is passed through a 150-mesh sieve and demagnetized using a super strong magnetic rod demagnetizer to obtain the target product (aqueous binder). The solid content of the aqueous binder is 10.1% and the viscosity is 18000cps.

[0119] Example 5

[0120] The aqueous binder provided in this embodiment includes a polymer having the following structure:

[0121]

[0122] Among them, a:b:c:d=30:20:20:30.

[0123] The preparation method of the water-based binder provided in this embodiment comprises the following steps:

[0124] 450 g of deionized water was added to the reactor at room temperature, and then 0.3 mol of acrylamide, 0.2 mol of methacrylic acid, 0.2 mol of vinyl diethylene glycol ether and 0.3 mol of acrylonitrile were added in sequence, and the mixture was stirred and dispersed at a stirring speed of 300 rpm. Nitrogen was introduced (nitrogen flow rate 2 L / h) for 1 hour to remove oxygen in the solution system (mixed solution), and then the temperature was raised to 50° C. After the temperature stabilized, 0.005 mol of initiator potassium persulfate was added to carry out polymerization reaction for 7 hours; the temperature was adjusted to 80° C., and then an oxidizing agent was added. 0.001 mol of reduced initiator ammonium persulfate and 0.001 mol of sodium bisulfite are used for polymerization reaction, and the reaction is carried out for 2 hours to remove residual monomers. After the reaction is completed, vacuum is evacuated for 1 hour to an absolute vacuum degree of 9 KPa to further remove residual monomers, and then lithium hydroxide monohydrate is added for neutralization to a pH value of 7.5, and deionized water is added for dilution to obtain a light yellow glue solution, which is sieved through a 150-mesh sieve and demagnetized using a super strong magnetic rod demagnetizer to obtain a target product (aqueous binder) having a solid content of 10.1% and a viscosity of 9000 cps.

[0125] Example 6

[0126] The aqueous binder provided in this embodiment includes a polymer having the following structure:

[0127]

[0128] Among them, a:b:c:d=40:30:15:15.

[0129] The preparation method provided in this embodiment is basically the same as that in embodiment 1, except that acrylamide is replaced by methacrylamide, and the solid content of the prepared aqueous binder is 10.2% and the viscosity is 12000 cps.

[0130] Example 7

[0131] The aqueous binder provided in this embodiment includes a polymer having the following structure:

[0132]

[0133] Among them, a:b:c:d=50:10:30:10.

[0134] The preparation method provided in this embodiment is basically the same as that in Example 1, except that 0.4 mol of acrylamide is replaced by 0.5 mol of the monomer corresponding to monomer unit a, 0.3 mol of acrylic acid is replaced by 0.1 mol of ethyl acrylic acid, 0.15 mol of vinyl glycol ether is replaced by 0.3 mol of vinyl propylene glycol ether, and 0.15 mol of acrylonitrile is replaced by 0.1 mol of the monomer corresponding to monomer unit d. The prepared aqueous adhesive has a solid content of 9.5% and a viscosity of 13100 cps.

[0135] Example 8

[0136] The aqueous binder provided in this embodiment includes a polymer having the following structure:

[0137]

[0138] Among them, a:b:c:d=40:30:15:15.

[0139] The preparation method of the water-based binder provided in this embodiment comprises the following steps:

[0140] 400 g of deionized water was added to the reactor at room temperature, and then 0.4 mol of N-isopropylacrylamide, 0.3 mol of isopropyl acrylic acid, 0.15 mol of vinyl glycol ether and 0.15 mol of acrylonitrile were added in sequence, and the mixture was stirred and dispersed at a stirring speed of 400 rpm. Nitrogen was introduced (nitrogen flow rate was 2 L / h) for 1 hour to remove oxygen in the solution system (mixed solution), and then the temperature was raised to 70° C. After the temperature stabilized, 0.001 mol of initiator potassium persulfate was added to carry out polymerization reaction for 6 hours; the temperature was adjusted to 90° C., and then 0.001 mol of redox initiator ammonium persulfate and 0.001 mol of sodium bisulfite are used for polymerization reaction, and the reaction is carried out for 1.5 hours to remove residual monomers. After the reaction is completed, vacuum is evacuated for 1 hour to an absolute vacuum of 30 KPa to further remove residual monomers, and then sodium hydroxide monohydrate is added for neutralization to a pH value of 7.5, and deionized water is added for dilution to obtain a light yellow glue solution, which is sieved through a 250-mesh sieve and demagnetized using a super strong magnetic rod demagnetizer to obtain a target product (aqueous binder) having a solid content of 10.5% and a viscosity of 23000 cps.

[0141] Example 9

[0142] The aqueous binder provided in this embodiment includes a polymer having the following structure:

[0143]

[0144] Among them, a:b:c:d=30:20:40:10.

[0145] The preparation method provided in this embodiment is basically the same as that in Example 1, except that 0.4 mol of acrylamide is replaced by 0.3 mol of N,N-dimethylacrylamide, 0.3 mol of acrylic acid is replaced by 0.2 mol of methacrylic acid, 0.15 mol of vinyl glycol ether is replaced by 0.4 mol of vinyl triethylene glycol ether, and 0.15 mol of acrylonitrile is replaced by 0.1 mol of the monomer corresponding to monomer unit d. The prepared aqueous adhesive has a solid content of 10% and a viscosity of 16800 cps.

[0146] Comparative Example 1

[0147] Styrene butadiene rubber (SBR) sold on the market by a certain company was used as a binder and was mixed with sodium carboxymethyl cellulose (CMC) in a mass ratio of 1:1.

[0148] Comparative Example 2

[0149] Acrylic resin PAA sold commercially by a certain company was used as the binder.

[0150] Comparative Example 3

[0151] The aqueous binder provided in this comparative example has the following structure:

[0152]

[0153] Among them, a:b:d=47:35:18.

[0154] The preparation method provided in this comparative example is basically the same as that in Example 1, except that no vinyl glycol ether is added, 0.47 mol of acrylamide, 0.35 mol of acrylic acid, and 0.18 mol of acrylonitrile.

[0155] Comparative Example 4

[0156] The aqueous binder provided in this comparative example includes a polymer having the structure shown below:

[0157]

[0158] Among them, a:b:c=47:35:18.

[0159] The preparation method provided in this comparative example is basically the same as that in Example 1, except that acrylonitrile is not added, 0.47 mol of acrylamide, 0.35 mol of acrylic acid, and 0.18 mol of vinyl glycol ether are added.

[0160] Comparative Example 5

[0161] The preparation method provided in this comparative example is basically the same as that in Example 1, except that "0.001 mol of redox initiators ammonium persulfate and 0.001 mol of sodium bisulfite" are replaced by "0.002 mol of potassium persulfate", and no redox initiators ammonium persulfate and sodium bisulfite are added.

[0162] Performance Testing

[0163] The binders prepared in Examples 1-9 and Comparative Examples 1-5 are used as binders for silicon negative electrode materials to prepare negative electrode sheets in the following manner:

[0164] The silicon-carbon composite material (using a silicon-based / graphite composite negative electrode material with a gram capacity of 600mAh / g), conductive carbon black, single-walled carbon nanotubes and the binder prepared in the embodiment or comparative example (the water-based binder prepared in the embodiment or comparative example, wherein the mass ratio of the solid in the water-based binder to the mass ratio of the silicon-carbon composite material is 6.25:93.0) are mixed, and the mass ratio of the silicon-carbon composite material, conductive carbon black, single-walled carbon nanotubes and the binder prepared in the embodiment or comparative example (based on the mass of the solid in the binder) is 93.0:0.5:0.25:6.25. Add an appropriate amount of deionized water at a ratio of 35% of the total solid content to prepare a battery electrode slurry. After the uniformly dispersed slurry is passed through a 100-mesh sieve, it is coated on a 10μm thick copper foil as a current collector, dried at 120°C for 5 minutes, and then sieved at room temperature with 10×10 4 The negative electrode sheet is obtained by rolling with a unit length load of N / m.

[0165] A 425060P lithium-ion battery is made with nickel cobalt manganese oxide NCM622 as the positive electrode, a mixed solvent of ethylene carbonate EC: ethyl methyl carbonate EMC: diethyl carbonate DEC in a mass ratio of 3:2:5, containing 1M LiPF6, as the electrolyte, and the existing PP material as the diaphragm.

[0166] The performance measurement method is as follows:

[0167] Determination of peel strength: The negative electrode sheet made of the binder prepared in the embodiment and the comparative example was cut into 10 cm × 2.5 cm strips, a 1 mm thick steel plate was adhered with double-sided tape on the collector side, and a transparent tape was pasted on the coating layer side. The strips were peeled off in the 180° direction at a speed of 100 mm / min using a tensile testing machine, and the peeling stress was measured.

[0168] Determination of the flexibility of the pole piece: a core rod with a diameter of Φ = 3 mm is placed on one side of the current collector of the rolled pole piece made of the adhesive prepared in the embodiment and the comparative example, and a bending test is performed. The state of the pole piece at this time is observed through an optical microscope. A good pole piece is marked as ○, and a pole piece that is detached or cracked is marked as ×.

[0169] Determine the first efficiency of the battery: At 25°C, in the voltage range of 2.5-4.2V, charge and discharge cycles are performed at 0.33C, and the constant current method is used to test the first coulombic efficiency of the charge and discharge cycle;

[0170] Determine the expansion at full charge: At 25°C, in the voltage range of 2.5 to 4.2V, perform two charge and discharge cycles at 0.33C, then fully charge the battery, disassemble the battery, and test the thickness d2 of the negative electrode. Assuming that the original thickness of the electrode is d1, the expansion rate at full charge is: (d2-d1) / d1×100%.

[0171] Determination of 300-cycle capacity retention rate: At 25°C, in the voltage range of 2.5-4.2V, charge at 0.5C and discharge at 1.0C for charge and discharge cycles. The constant current method is used to test the capacity retention rate after 300 cycles. Capacity retention rate = gram capacity in the 300th cycle discharge / gram capacity in the 1st cycle discharge.

[0172] The test results are shown in Table 1 and Table 2.

[0173] Table 1

[0174]

[0175] Table 2

[0176] project Example 7 Example 8 Example 9 Peel strength (N / m) 76.21 74.28 73.69 Pole flexibility ○ ○ ○ First effect (%) 85.30 85.24 85.27 Full charge expansion (%) 35.89 36.34 36.18 300-cycle capacity retention rate (%) 81.18 80.92 80.71

[0177] It can be seen from Table 1 and Table 2 that, relative to commercially available SBR (Comparative Example 1), the binders provided in Examples 1-9 have very obvious improvements in peel strength, first effect, full-charge expansion and cycle retention rate; relative to commercially available PAA binders (Comparative Example 2), the binders provided in Examples 1-9 have also significantly improved in peel strength, electrode flexibility, first effect, full-charge expansion and cycle retention rate. This shows that the aqueous binder provided by the present invention has excellent bonding properties, can significantly inhibit the expansion of the silicon negative electrode, and at the same time makes the prepared electrode have excellent flexibility, thereby improving the cycle performance of the battery.

[0178] Compared with Example 1, in Comparative Example 3, no vinyl glycol ether was added during the preparation of the binder, resulting in poor flexibility of the pole piece and a significant decrease in cycle performance.

[0179] Compared with Example 1, in Comparative Example 4, acrylonitrile was not added during the preparation of the adhesive, resulting in a decrease in the peel strength of the pole piece.

[0180] Compared with Example 1, in Comparative Example 5, redox initiators ammonium persulfate and sodium bisulfite were not added during the preparation of the binder, resulting in reduced peel strength, first effect and cycle performance of the pole piece.

[0181] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A water-based adhesive, characterized in that: The aqueous binder includes a polymer containing at least three monomer units, wherein the polymer is composed of a first monomer unit, a second monomer unit and a third monomer unit, or is composed of a first monomer unit, a second monomer unit, a third monomer unit and a fourth monomer unit, wherein the first monomer unit has a structure shown in formula I, the second monomer unit has a structure shown in formula II, and the third monomer unit has a structure shown in formula III, Wherein, R1, R2, R3 and R6 are the same or different and each independently represents hydrogen, a linear alkyl group or a branched alkyl group; R5 is a group having a hydroxyl group at the end; The fourth monomer unit has a structure shown in Formula IV: wherein R4 represents hydrogen, a linear alkyl group or a branched alkyl group; M represents H, Li, Na or K; The polymer has a structure shown in Formula V: Ⅴ Wherein, R1, R2, R3 and R6 are the same or different and independently represent hydrogen, linear alkyl or branched alkyl; R5 is a group having a hydroxyl group at the end; R4 represents hydrogen, linear alkyl or branched alkyl; M represents H, Li, Na or K, and a:b:c:d=(30-80):(0-50):(5-50):(10-30); when the polymer is composed of the first monomer unit, the second monomer unit and the third monomer unit, b=0, and a:c:d=(30-80):(5-50):(10-30); Taking the total molar number of the acrylamide monomer, the acrylic acid monomer, the vinyl ether monomer and the acrylonitrile monomer as 100%, the molar percentage of the acrylonitrile monomer is 10% to 30%; The polar groups -OH, -CONR2R3 and -CN in the polymer form hydrogen bonds or chemical bonds with silicon particles in the silicon negative electrode, forming a three-dimensional network structure.

2. The aqueous adhesive according to claim 1, characterized in that The R5 represents a straight-chain alkyl group having 1 to 6 carbon atoms substituted by a hydroxyl group, a branched-chain alkyl group having 1 to 6 carbon atoms substituted by a hydroxyl group, -CH2CH2OCH2CH2OH or -(CH2CH2O) n H, n≥3; And / or, the R1, R2, R3 and R6 are the same or different, and each independently represents hydrogen, a straight-chain alkyl group having 1 to 6 carbon atoms, or a branched-chain alkyl group having 1 to 6 carbon atoms.

3. The aqueous adhesive according to claim 1, characterized in that: R5 represents -CH2CH2OH, CH2CH2CH2OH, -CH2CH2OCH2CH2OH or -(CH2CH2O) n H, n≥3; the R1 represents hydrogen, methyl, ethyl, propyl, -CH(CH3)2, -CH2CH2CH2CH3 or -CH2CH(CH3)2; the R2 represents hydrogen, methyl, ethyl, propyl, -CH(CH3)2, -CH2CH2CH2CH3 or -CH2CH(CH3)2; the R3 represents hydrogen, methyl, ethyl, propyl, -CH(CH3)2, -CH2CH2CH2CH3 or -CH2CH(CH3)2; the R6 represents hydrogen, methyl, ethyl or -CH(CH3)2.

4. The aqueous adhesive according to claim 1, characterized in that: R4 represents hydrogen, a straight-chain alkyl group having 1 to 6 carbon atoms, or a branched-chain alkyl group having 1 to 6 carbon atoms; And / or, the aqueous binder has a solid content of 9.5-10.5% and a viscosity of 8000-30000 cps.

5. A method for preparing a water-based binder as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: Under the action of an initiator, the polymer monomers undergo a polymerization reaction in a reaction solvent to obtain the water-based binder, wherein the polymer monomers include acrylamide monomers, vinyl ether monomers and acrylonitrile monomers.

6. The method for preparing the aqueous binder according to claim 5, characterized in that: The polymer monomer further comprises an acrylic monomer, and the molar ratio of the acrylamide monomer, acrylic acid monomer, vinyl ether monomer and acrylonitrile monomer is (30-80): (0-50): (5-50): (10-30); The polymer monomers are polymerized in a reaction solvent under the action of an initiator to obtain the water-based binder, comprising the following steps: S1, adding the polymer monomer into a reaction solvent, stirring and dispersing, and obtaining a mixed solution; S2. Add a first initiator to the mixed solution to carry out a first polymerization reaction, then add a second initiator to carry out a second polymerization reaction, and after the reaction is completed, vacuumize, neutralize with alkali, screen, and demagnetize to obtain the aqueous binder, wherein the molar ratio of the first initiator to the second initiator is (0.5~3):1, the first initiator includes at least one of sodium persulfate, potassium persulfate, and ammonium persulfate, and the second initiator is a redox initiator including at least one of ammonium persulfate / sodium sulfite, ammonium persulfate / sodium bisulfite, and hydrogen peroxide / ferrous ion.

7. The method for preparing the aqueous binder according to claim 6, characterized in that: The temperature of the first polymerization reaction is 40° C. to 80° C., and the time is 3 to 10 hours; the temperature of the second polymerization reaction is 70° C. to 90° C., and the time is 1 to 3 hours.

8. Use of the aqueous binder according to any one of claims 1 to 4 or the aqueous binder prepared by the method for preparing the aqueous binder according to any one of claims 5 to 7, characterized in that: The aqueous binder is used for preparing lithium ion batteries.

Citation Information

Patent Citations

  • Binder solution for lithium ion battery electrode, slurry for lithium ion battery electrode, lithium ion battery electrode, and lithium ion battery

    CN112447973A